We regret to inform you - Kaplan, A. E. (2018)
Mischa Abramavicius is a walking, talking, top-scoring, perfectly well-rounded college application in human form. When all of her college applications are rejected-- even her safety school-- she is shocked and devastated. Grappling with the prospect of an uncertain future, she begins to believe that her transcript was hacked. With the help of her best friend and sometimes crush, Nate, and a group of eccentric techies known as "The Ophelia Syndicate," Mischa launches an investigation that will shake the quiet community of Blanchard Prep to its stately brick foundations
Keywords: College choice -- Juvenile fiction; Hackers -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Preparatory school students -- Juvenile fiction; Detective and mystery stories; Young adult fiction; Hackers -- Juvenile fiction; Friendship -- Juvenile fiction; Hackers -- Fiction; High schools -- Juvenile fiction; High schools -- Fiction; College choice -- Juvenile fiction; College choice -- Fiction; Universities and colleges -- Admission -- Juvenile fiction; Universities and colleges -- Admission -- Fiction; Female friendship -- Juvenile fiction